Moral Competence in Nursing Practice amongst Nursing Students at Prince of Songkla University - Prompahakul, Chuleeporn; Nilmanat, Kittikorn (Journal of Thailand Nursing and Midwifery Council, 2018)
Abstract Objective: To examine the level of moral competence amongst nursing students at Prince of Songkhla University in their nursing practice. Design: Cross-sectional descriptive study. Methodology: The sample consisted of 417 second- to fourth-year nursing students who possessed some clinical practice experience. Data were collected using (i) a personal information form; (ii) a moral competence questionnaire; and (iii) a questionnaire on learning activities in clinical practicum for the promotion of moral competence. The questionnaires’ respective reliability scores were 0.94 and 0.87. The data were analysed using descriptive statistics and one-way ANOVA. Results: Overall, the participants displayed a very high level of moral competence (mean = 4.23, SD = 0.51). In addition, a difference in moral competence was found between the second-year students and the third- and fourth-year students. The participants were of the opinion that a post-nursing conference, reﬂective thinking and case study seminar could most effectively increase their moral competence. Recommendations: It is suggested that a nursing institute organise on-going activities to increase the students’ moral competence. Recommended activities include post-nursing conference, reﬂective thinking and case study seminars. It is also suggested further studies be conducted on factors inﬂuencing nursing students’ moral competence.